Nīlū, Nīlimā, Nīlofara - Sāhanī, Bhīṣma 1915-2003 (Rājakamala Prakāśana, 2010)
Based on the issue of communalism in post 1947 India
In Devanagari-Schrift, Hindi. - Novel
Keywords: Geschichte 1900-2000; Hindi fiction / 20th century